Pemahaman dan Penghayatan Siswa/I SMP Stella Duce II Yogyakarta akan Makna Kehadiran Kristus dalam Ekaristi - Dwiatmaja, Alb Irawan (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2022)
This study aims to determine the extent of understanding and appreciation of the students of Junior High School of Stella Duce II grade 8th Yogyakarta on the meaning of Christ's presence in the Eucharist. The author assumes that the Eucharist as the pinnacle and source of Christian life should be a pattern of life and should permeate every Catholic. It must be admitted that in general people of all age groups are diligent in following the Eucharist. From the age group that participates in the Eucharist, the author is interested in conducting research on the adolescent age group, specifically for junior high school students. The object of the author's research is addressed to the students of Junior High School of Stella Duce II grade 8th who become acolytes and lectors. The main issue discussed is how the Catholic youth Stella Duce II Junior High School of grade 8th who are assigned to be acolytes and lectors know, feel, and experience the presence of Christ in their duties and participation in the celebration of the Eucharist. In this study, the authors used quantitative and qualitative research methods.